Maqāṣid al-Sharī‘ah sebagai Landasan Dasar Ekonomi Islam - Dani Rohmati; Rachmasari Anggraini; Tika Widiastuti (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2018)
Islam exists and is trusted by its adherents as a doctrine that regulates all forms of human activity universally and comprehensively, between human beings as creatures with God as their Creator and human beings as fellow creatures of His creation. Muslims will never be free from all kinds of economic activities, therefore as Muslims in their economic activities must be based on Islam in order to get welfare and maslahah. Then the purpose of this study will researching in more detail about the foundations of Islamic economics and Maqāṣid al-Sharī‘ah so that in the economic activities of Muslims get falah and maslahah. The hope of the results of this study can be used as a reference for both readers and writers.Islam ada dan dipercaya oleh para pengikutnya sebagai doktrin yang mengatur semua bentuk aktivitas manusia secara universal dan komprehensif, antara manusia sebagai makhluk dengan Tuhan sebagai Pencipta dan manusia sebagai sesama makhluk ciptaan-Nya. Muslim tidak akan pernah bebas dari segala macam kegiatan ekonomi, oleh karena itu sebagai Muslim dalam kegiatan ekonomi mereka harus didasarkan pada Sharī‘ah untuk mendapatkan kesejahteraan dan maslahah. Maka tujuan penelitian ini akan meneliti secara lebih detail tentang pondasi ekonomi Islam dan Maqāṣid al-Sharī‘ah sehingga dalam kegiatan ekonomi umat Islam mendapatkan kesejahteraan dan maslahah. Harapan hasil penelitian ini dapat dijadikan referensi baik pembaca maupun penulis.